أغراض خطابة الإمام الخميني و خصائص أسلوبها - Iqbal, Muhammad (Buletin Al-Turas, 2013)
AbstractAl-Khumayni is the first Iranian Supreme Leader had a big hand in the Iranian revolution. He was born on 24 September 1902 in Khomein, Markazi Province. Together with his followers in the city of Qum, al-Al-Khumayni began to build a political base against the royal family especially the Shah of Iran Mohammed Reza Pahlavi, who later became an important part of the power steering Iran's Islamic Revolution. The main weapon held by al-Khumayni was political speeches capable of moving masses in large numbers so as to make future milestone Iranian empire felled. He was a great orator capable of sorting out the words and put them into a strand of pearls that evoke a spirit listeners to dissolve in their struggle against the Iranian royal family and American intervention. The style of language in his speech (Uslub Khithaby) which was the rhetorical speech trigger the urge author to analyze it more deeply through one of his speeches was phenomenal "American intervention in Iranian affairs".---AbstractAl-Khumayni is the first Iranian Supreme Leader had a big hand in the Iranian revolution. He was born on 24 September 1902 in Khomein, Markazi Province. Together with his followers in the city of Qum, al-Al-Khumayni began to build a political base against the royal family especially the Shah of Iran Mohammed Reza Pahlavi, who later became an important part of the power steering Iran's Islamic Revolution. The main weapon held by al-Khumayni was political speeches capable of moving masses in large numbers so as to make future milestone Iranian empire felled. He was a great orator capable of sorting out the words and put them into a strand of pearls that evoke a spirit listeners to dissolve in their struggle against the Iranian royal family and American intervention. The style of language in his speech (Uslub Khithaby) which was the rhetorical speech trigger the urge author to analyze it more deeply through one of his speeches was phenomenal "American intervention in Iranian affairs".